Effect of alkali fusion temperature on the synthesis and characteristics of nanosilica from silica sand - Muhammad Sadat Hamzah; Muchsin Muchsin; Abdul Muis; Dino Hasyim; Iqrham Dwi Putra Annas; Muhammad Syaiful Fadly; Bakri Bakri; Sri Chandrabakty (Jurnal Polimesin, 2026)
The increasing demand for nanosilica in industrial applications has encouraged the utilization of abundant natural silica sand as a sustainable raw material. This study investigates the effect of alkali fusion temperature on the synthesis and characteristics of nanosilica derived from silica sand from Central Sulawesi, Indonesia. A cost-effective, energy-efficient synthesis method is needed to transform raw sand into high-value nanoparticles with controlled morphology. The study employed the alkali fusion method, where silica sand was reacted with NaOH at temperatures ranging from 400°C to 700°C, followed by leaching and titration to pH 7-8 to produce nanosilica. Characterization results via XRF and XRD confirmed that the synthesized nanosilica maintains a high SiO2 concentration (up to 72.46%) and exhibits a coexistence of amorphous phases and crystalline quartz. Morphological analysis by TEM revealed that increasing the fusion temperature decreases particle size from 18.91 nm at 400°C to 14.00 nm at 700°C, indicating that higher thermal energy promotes structural decomposition. These findings suggest that the alkali fusion temperature is an important parameter for controlling nanosilica dimensions. Further evaluation, including yield and recovery analysis, is required to assess process efficiency and its potential for large-scale applications.